KOLABORASI PENULIS PADA KONFERENSI PERPUSTAKAAN DIGITAL INDONESIA PERIODE 2013–2018 - Rochani Nani Rahayu; Tupan Tupan (Perpustakaan Nasional RI, 2019)
This study focused on papers from the proceedings of the Conference of the Indonesian Digital Library (KPDI) within the period of 2013-2019, accessed from the KPDI website using the bibliometric method. The main purposes of the study were to identify 1) distribution of papers based on years; 2) number of single writers and collaborative writers 3) authorship patterns; 4) degree of collaborative writing; 5) number of average writers per paper and 6) productivity of writers. The results showed that from the 102 papers presented at the conference by 147 writers, the composition of papers written by single writers was 69 titles (67.65%) and by collaborative writers was 33 titles (32.35%). This is reflected in the pattern of authorship as follows. Single writer of 69 titles (67.65%), then papers written by two persons of 22 titles (21.56%), papers written by three persons of 10 titles (9.80%) and by four persons of 1 title (0.98%) The degree of collaborative writing was 0.32. The average number of writers per paper was 1.44 and Deden Sumirat was the most active writer who contributed 5 titles. It can be concluded that collaborative writings have not been highly performed in KPDI.